Kecemasan dan Persepsi Pasien Kanker Ovarium dengan Kemoterapi setelah Terapi Smartphone-Based Virtual Reality (S-VR): Studi Kasus - Made Satya Nugraha Gautama; Wiwin Lismidiati; Farida Widayati (PSIK FKKMK UGM, 2021)
Background: Chemotherapy is a systemic modality for cancer patients and has physical and psychological side effects. Psychological problems usually arise most often when undergoing chemotherapy. Not a few patients feel anxiety and negative perceptions when diagnosed with cancer, undergo surgery, or have an IV inserted to get chemotherapy drugs. Virtual Reality (VR) is a technology-based non-complementary therapy that has the potential to be involved as an alternative in the management of symptoms of cancer patients.Objective: To describe the effects of using Smartphone-Based Virtual Reality (S-VR) on the level of anxiety and perceptions of cancer patients during chemotherapy.Methods: A case study of ovarian cancer patient undergoing chemotherapy and were given Smartphone -Based Virtual Reality (S-VR) treatment.Results: The results obtained were a decrease in situational anxiety facing chemotherapy from a score of 40 (moderate anxiety) to a score of 21 (mild anxiety), decreased in pulse rate, and a significant increase in the perception score (28.6%) (less perception) to 94.3% ( good perception) after getting S-VR intervention during chemotherapy.Conclusion: S-VR can be a technology-based and non-invasive non-pharmacological intervention in reducing anxiety and providing positive experiences for patients during chemotherapy. ABSTRAKLatar Belakang: Tidak sedikit pasien merasakan kecemasan dan persepsi negatif saat didiagnosa kanker, menjalankan pembedahan, atau dipasang infus kemoterapi. Virtual Reality (VR) menjadi salah satu terapi non-komplementer berbasis teknologi yang potensial dilibatkan sebagai alternatif dalam manajemen gejala pasien kanker.Tujuan: Untuk mengetahui efek penggunaan Smartphone-Based Virtual Reality (S-VR) terhadap tingkat kecemasan dan persepsi pasien kanker selama menjalani kemoterapi.Metode: Studi kasus dilakukan pada pasien dengan kanker ovarium yang mendapatkan kemoterapi dan diberikan terapi S-VR. Kecemasan diukur dengan instrument S-AI, pengukuran nadi dan RR. Pengukuran persepsi menggunakan instrument dari Scates.Hasil: Terjadi penurunan kecemasan saat kemoterapi dari skor 40 (kecemasan sedang) ke skor 21 (kecemasan ringan), penurunan frekuensi nadi dan adanya peningkatan secara signifikan skor persepsi (65,7%) (persepsi cukup) menjadi 94,3% (persepsi baik) setelah mendapatkan intervensi S-VR selama kemoterapi.Kesimpulan: S-VR dapat menjadi intervensi non-farmakologis berbasis teknologi dan non-invasif dalam menurunkan kecemasan dan memberikan pengalaman positif pada pasien selama menjalani kemoterapi.Kata Kunci: